CARDIOVASCULAR DISEASES AND THEIR PRACTICAL SIGNIFICANCE (Modern education and development, 2025)
This article analyzes common cardiovascular diseases, their causes, prevention and treatment, preventive measures, and the organs in which the disease occurs, their structure and function. The article also examines methods for identifying and diagnosing circulatory system diseases based on international experience. The article discusses the function, importance, and mechanism of the cardiovascular system in the human body.